Experiences in the culture of new species in the 'Estación de Acuicultura' of the Balearic Government (1980-1998) - Pastor E.; Riera F.; Massutí E.; Grau A.M.; Grau A.; Pou S. (Recent advances in Mediterranean aquaculture finfish species diversification, 2000)
This paper is a review of the diverse results on marine finfish aquaculture diversification obtained at the 'Estación de Acuicultura' (Port of Andratx, Majorca) from its beginnings to nowadays. We expose the results obtained with the main finfish Mediterranean species investigated, briefly describing the capture of the individuals from the natural environment, the breeding, rearing and ongrowing technics, as well as the main pathological problems observed in our aquaculture facilities. We resume our results obtained with three finfish species: the amberjack, Seriola dumerili (Risso, 1810), the common dentex, Dentex dentex (Linnaeus, 1758) and the sharpsnout sea bream, Diplodus puntazzo (Cetti, 1777).
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean on 'Recent advances in Mediterranean aquaculture finfish species diversification', 1999/05/24-28, Zaragoza (Spain)